Substrate-borne vibrations produced during the interaction with natural enemies alter aphids probing behavior - Caterina Zippari; Rachele Nieri; Zeinab Hamouche; Abderrahmane Boucherf; Giovanni Tamburini; Gianfranco Anfora; Vincenzo Verrastro; Valerio Mazzoni; Daniele Cornara (Journal of Pest Science, 2024)
The “ecology of fear”, i.e., physiological and behavioral alterations displayed by pests in response to predation risk, has recently been proposed as a sustainable alternative to chemicals for pest control. However, the development of such a strategy requires a detailed understanding of the signals and cues underlying the pest-antagonist interaction and eliciting the prey behavioral alteration. Here, we characterized the substrate-borne vibrations produced during the interaction between the green peach aphid Myzus persicae and its antagonists, the parasitoid wasp Aphidius colemani and the ladybug Adalia bipunctata. Thereafter, coupling the electrical penetration graph (EPG) with a stimulus controller, we evaluated whether the playback of the vibrations, alone and in combination with the alarm pheromone, impacted aphid probing behavior and interaction with the host plant. Aphids responded to vibrations exhibiting longer non-probing, shorter intracellular probes, i.e. the behavior through which the insect evaluates host plant quality, delay in accessing the phloem vessels and decrease of the frequency of phloem salivation events. In contrast, on plants treated with the alarm pheromone, insects displayed longer intracellular probes. We hypothesize that the alarm pheromone, signaling a distant threat, might induce a careful evaluation of the host plant in order to decide the magnitude of the reaction. On the other hand, vibrations might indicate a closely approaching threat pushing the aphid to rush the host evaluation process and the whole feeding process. The possible repercussion of the behavioral alterations observed on the dynamics of aphid-borne plant virus transmission is also discussed.